Efektivitas Penerapan Aplikasi Sistem Informasi Manajemen BAZNAS (SIMBA) Pada Pelaporan Pengelolaan Dana Zakat Infak Dan Sedekah BAZNAS Kabupaten Banyumas - Siti Jubaedah Anuri; Ma’ruf Hidayat (JURNAL ILMIAH NUSANTARA, 2024)
. Reporting on the management of ZIS funds through SIMBA is an effort to realize accountable and transparent management. By knowing the effectiveness of the management information system (SIMBA) used by BAZNAS Banyumas Regency, we can see the level of efficiency in achieving the reporting objectives of managing zakat, infaq and alms funds at BAZNAS Banyumas Regency. The aim of this research is to show how effective the application of the SIMBA application is in reporting, supporting and inhibiting factors in the management of BAZNAS zakat, infaq and alms funds in Banyumas Regency. Data collection was carried out using interview techniques with all SIMBA Admins at BAZNAS Banyumas, observation and documentation. Data analysis techniques include data collection, data reduction, data presentation, data verification and drawing conclusions. The research results show that: 1) The effectiveness of the SIMBA application in reporting management and zakat infaq and alms is proven by its ease, integration and accuracy; 2) Supporting factors include accountability, transparency and speed. Meanwhile, the obstacles found were that SIMBA was still dependent on internet connections, especially during maintenance, inadequate device infrastructure to be used and lack of admin training for the latest features. Another factor is the lack of in-kind zakat features.